2019
DOI: 10.3389/fgene.2019.01206
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape Genetic Signature of Pollination by Trapliners: Evidence From the Tropical Herb, Heliconia tortuosa

Abstract: Animal-mediated pollination is essential for the maintenance of plant reproduction, especially in tropical ecosystems, where pollination networks have been thought to have highly generalized structures. However, accumulating evidence suggests that not all floral visitors provide equally effective pollination services, potentially reducing the number of realized pollinators and increasing the cryptic specialization of pollination networks. Thus, there is a need to understand how different functional groups of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 86 publications
2
20
0
Order By: Relevance
“…This ‘high‐mobility’ foraging strategy can potentially increase outcrossing and mate diversity by facilitating the receipt of non‐self and unrelated pollen (Ohashi & Thomson, 2009). Our recent work showed that hierarchical patterns of pollen pool differentiation (quantified among forest patches and among neighbouring H. tortuosa individuals within forest patches) were consistent with the foraging strategy of high‐mobility traplining hummingbirds, as neighbouring H. tortuosa individuals were found to sample genetically distinct pollen pools (Torres‐Vanegas et al., 2019). This suggests that these species are largely responsible for effective pollen transfer in H. tortuosa (Torres‐Vanegas et al., 2019).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…This ‘high‐mobility’ foraging strategy can potentially increase outcrossing and mate diversity by facilitating the receipt of non‐self and unrelated pollen (Ohashi & Thomson, 2009). Our recent work showed that hierarchical patterns of pollen pool differentiation (quantified among forest patches and among neighbouring H. tortuosa individuals within forest patches) were consistent with the foraging strategy of high‐mobility traplining hummingbirds, as neighbouring H. tortuosa individuals were found to sample genetically distinct pollen pools (Torres‐Vanegas et al., 2019). This suggests that these species are largely responsible for effective pollen transfer in H. tortuosa (Torres‐Vanegas et al., 2019).…”
Section: Introductionmentioning
confidence: 73%
“…Our recent work showed that hierarchical patterns of pollen pool differentiation (quantified among forest patches and among neighbouring H. tortuosa individuals within forest patches) were consistent with the foraging strategy of high‐mobility traplining hummingbirds, as neighbouring H. tortuosa individuals were found to sample genetically distinct pollen pools (Torres‐Vanegas et al., 2019). This suggests that these species are largely responsible for effective pollen transfer in H. tortuosa (Torres‐Vanegas et al., 2019). As such, the next important step is to understand how deforestation and reduced abundance of high‐mobility traplining hummingbirds impact plant mating quality.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The flowers of H. tortuosa can recognize and favor pollination by traplining hummingbirds over territorial hummingbirds, as only trapliners fully drain the available nectar – the signal that triggers pollen tube growth (Betts et al ., 2015). This pollinator recognition mechanism results in high realized pollen dispersal, as is expected for pollination by trapliners (Torres‐Vanegas et al ., 2019). The prevalence of such recognition systems is unknown.…”
Section: Studies Confirm That Highly Mobile Pollinators Promote Outcrmentioning
confidence: 99%
“…This species harbors a diversity of organisms beneficial to the environment (Benítez-Malvido et al, 2019;Janeček et al, 2019), and provide an ideal habitat for the development of the biological cycle of some insects corresponding to the orders: Diptera, Coleoptera, Himenoptera y Hemiptera, due to the different phenological, structural and environmental conditions generated in the crops (Henao and Ospina, 2008;Foottit and Maw, 2019). Furthermore, these species are mainly pollinated by hummingbirds and bats (Temeles and Bishop, 2019;Torres-Vanegas et al, 2019). The latter are used by heliconia plants for reproduction and survival; rolled tubular sheets provide microclimatic conditions suitable for tropical species and benefit camouflage (Pérez-Cárdenas et al, 2019; Rodríguez-Herrera et al, 2019).…”
Section: Productionmentioning
confidence: 99%